Cuidados de enfermería en prevención de desnutrición crónica en niños menores de un año del Centro De Salud Junta Nueva, Cantón Babahoyo Vía Febres Cordero, periodo octubre 2019-marzo 2020. - Sánchez Zerna, Kevin Axel (2020)
Introduction: Chronic malnutrition is a factor that influences the growth and development of the child, considered as a public health problem that affects a large population group. Chronic malnutrition is mainly due to lack of nutrients necessary for the health and proper functioning of the body such as: vitamin A, folic acid, iodine, protein or iron; but other factors also affect, such as the lack of access to drinking water, often causing permanent diarrhea, thus preventing the correct assimilation of nutrients. Objective: To determine the nursing care in prevention of chronic malnutrition in children under one year of the Junta Nueva Health Center, Babahoyo canton via Febres Cordero, period October 2019 - March 2020. Methodology: The scientific field research will use the descriptive - quantitative method which will allow to describe and quantify the risk factors that cause chronic malnutrition in children under one year of age and will serve as necessary information for the investigation. Results: the data were analyzed in the Microsoft Excel program where it was found that a high percentage of the population has knowledge about exclusive breastfeeding but its roots are very based on giving the child banana flour (pouring) from the first months of life, so the child does not receive the proteins and nutrients necessary for their growth and development. Conclusion: Nursing care in prevention of chronic malnutrition helps prevent health problems in children caused by nutrient deficits.